TENDON TRANSFERS FOR RADIAL NERVE PALSY - Nur Rachmat Lubis; Wiria Aryanta; Davin Caturputra Setiamanah (Majalah Kedokteran Sriwijaya, 2020)
Background: High radial nerve palsy mostly caused by injury of nerve branching from proximal to the elbow resulting in function loss of wrist, finger and thumb extension, as well as thumb abduction. Tendon transfers are the most common technique for motor reconstruction indicated in high radial nerve palsy if the patients fail to achieve nerve regeneration and recovery. This procedure will restore finger, thumb, and wrist function, without foisting other motoric deficits on the hand, with satisfying results. Case: 19 years old male was referred to RSUP dr. Mohammad Hoesin Palembang with right wrist joint instability and limited range of motion (ROM). Past history of fracture at the middle third of the right humerus 6 months ago. Physical examination showed total loss of active wrist extension, thumb extension and abduction, and finger extension at metacarpophalangeal (MCP) joints. The patient is diagnosed as a high lesion of radial nerve palsy. Tendon transfers procedure were prepared to restore better wrist function and ROM. Tendon transfers performed with Riordan method, using pronator teres as extensor carpi radialis brevis for wrist extension, flexor carpi ulnaris to extensor digitorum communis for finger extension, palmaris longus to extensor pollicis longus for thumb extension. Conclusion: Tendon transfers for high radial nerve palsy is an effective technique to restore the function of wrist extension, finger extension, and power of handgrip.